The effectiveness of the rhythm of alliteration in the poetry of Abu Tammam (231 H) (Journal of Hama University, 2026)
The research seeks to study the effectiveness of the rhythm of alliteration in Abu Tammam’s poetry through a semantic-rhythmic study. Therefore, the research begins with an introduction that includes a discussion of the meaning of the term, then it proceeds to study the internal density of alliteration, through studying two features: total density and partial density. This is then followed by a study of the external density of alliteration, which also falls into two features: consonant density and vowel density.To prove the ability of alliteration to raise the pace of the internal music of the text, and its function does not stop at the limits of the rhythmic level only; rather, it extends to the semantic and emotional levels, thus achieving what the text needs in terms of coherence and connectionThe Keywords: Abu Tammam, assonance, rhythm, meaning, cohesion.
Keywords: The Keywords: Abu Tammam, assonance, rhythm, meaning, cohesion.